Development and implementation of an opensource DIC acquisition system, focusing on temporal synchronization with the Gleeble 3800 - Vos, Maxwell (Department of Mechanical Engineering, 2026)
The Gleeble 3800 is a thermomechanical processing simulator with the ability to perform high temperature, high strain rate deformation experiments. The standard Gleeble 3800 uses electrical resistance heating for temperature control and a closed loop hydraulic actuator for displacement control. In order to extract greater accuracy and control of simulated processing parameters, the incorporation of a synchronised Digital Image Correlation (DIC) capability with equipment such as the Gleeble 3800 has become essential. Current commercial DIC systems offer limited versatility, particularly with regards to integrating DIC and thermal imaging on the Gleeble 3800 in addition to being financially prohibitive for many researchers. Current open-source acquisition solutions lack the specifications required for most DIC applications and custom solutions are overly complex for many DIC users. This research therefore aimed to develop an open-source DIC acquisition system for materials research applications that fulfil these shortcomings. The DIC Capture system addresses these limitations by using high quality hardware that interfaces with user orientated software, thus facilitating complex material testing protocols at a reduced cost. The DIC Capture system comprises of a hardware data acquisition (DAQ) board, full field camera system and control computer. The DAQ is controlled by an Arduino Nano ESP32 that sends camera trigger times, voltage values from the ±10V ADS8584S analogue to digital converter (ADC) and sync times with the Gleeble 3800. The camera trigger frequency follows a predetermined sequence and is iterated through a command in the Gleeble Script Language (GSL) program, which controls the Gleeble 3800, thus allowing for event-based frame-rate changes. The Python based software displays and saves images from the DIC cameras, synchronizing all data received from the DAQ board and any other image recording sources. The DIC Capture system can produce high quality DIC data sets and integrates with the Gleeble 3800 for high temperature DIC applications. The DIC capture system has been successfully tested in three different case studies across a range of testing conditions.